Changes in Serum TSH and T4 Levels after Switching the Levothyroxine Administration Time from before Breakfast to before Dinner - S. Ala; O. Akha; Z. Kashi; A. Bahar; H. Askari Rad; N. Sasanpour; A. Shiva (International Journal of Endocrinology)
Background. Levothyroxine is commonly used in the treatment of patients with hypothyroidism. Levothyroxine is most often administered in the morning, on an empty stomach, in order to increase its oral absorption. However, many patients have difficulties taking levothyroxine in the morning. Aim. The aim of this study was evaluating the effect of changing levothyroxine administration time from before breakfast to before dinner on the serum levels of TSH and T4. Subjects and Methods. Fifty patients between 18 and 75 years old with hypothyroidism were included in the study and were randomly divided into two groups. Each group received two tablets per day (one levothyroxine tablet and one placebo tablet) 30 minutes before breakfast and 1 hour before dinner. After two months, the administration time for the tablets was changed for each group, and the new schedule was continued for a further two-month period. The serum TSH and T4 levels were measured before and after treatment in each group. Results. Changing the levothyroxine administration time resulted in 1.47 ± 0.51 µIU/mL increase in TSH level (p=0.001) and 0.35 ± 1.05 µg/dL decrease in T4 level (p=0.3). Conclusions. Changing the levothyroxine administration time from before breakfast to before dinner reduced the therapeutic efficacy of levothyroxine.